High-hardness high-binding-force colorful composite film on plastic surface and preparation method thereof
By using magnetron sputtering technology to deposit a multi-layer film structure on the plastic surface, the existing colored plastic products have been solved, such as uneven surface color, poor chemical dye stability, easy fading, and low hardness, and high binding force are achieved. , colored fantasy composite film with wide color gamut and long-term stability.
Patent Information
- Application Number
- CN202510002023.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2045-01-02
AI Technical Summary
Existing colored plastic products have uneven surface colors, poor chemical dye stability, easy fading, low hardness and difficulty in achieving wide color gamut, high hardness, high binding force, low cost manufacturing, long-term stability and variability in perspective .
The Ti seed layer, Al layer, TiN layer, TiAlN layer and AlN layer are deposited in sequence through magnetron sputtering technology to build a multi-layer film structure to improve film-based binding force, color brightness and color gamut range, and generate it through the film interference effect Fantasy effect.
The colored fantasy composite film with high hardness, high binding force, wide color gamut, long-term stability and variability in viewing angles has been achieved, which significantly improves the protection effect and color saturation of plastic products.
Smart Images

Figure CN119392172A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of multilayer films, and in particular to a colorful composite film with high hardness and high bonding strength on a plastic surface and a preparation method thereof. Background Art
[0002] Colored plastics are widely used in art decorations, toys, packaging, automobiles and other industries due to their diverse colors, low cost and easy processing. Iridescent plastics are more often used in high-end markets and design fields. Their special optical effects give products stronger visual impact and artistic sense, and are widely used in creative art, automobiles and luxury goods.
[0003] The production methods of traditional colored plastics and iridescent plastics with special visual effects such as color change, gradient, metallic luster, etc. usually rely on the use of pigments, dyes or other special additives to achieve unique color effects. The colored plastics on the market now are usually formed by adding pigments or dyes to the resin or coating the surface of the product during the plastic processing and production process. However, the poor compatibility of the resin in the molten state with inorganic pigments will lead to uneven color on the surface of the plastic product, and more importantly, some colored plastics made of chemical dyes have poor long-term stability and will degrade over time, thereby losing their chroma and brightness. The direct coating method will cause the plastic product to fade easily due to the poor bonding between the coating and the plastic surface. In addition, the surface hardness of the colored plastics made by these methods is low, and scratches and cracks are prone to occur during the manufacturing and transportation process. And it is difficult to achieve a iridescent effect by simply using chemical dyes or coatings. Therefore, there is an urgent need for physical structural color plastic products with color and iridescent effects. However, in practical applications, it is still a daunting challenge to simultaneously achieve a wide color gamut, high hardness, high bonding, low-cost manufacturing, long-term stability and viewing angle variability of structural colors.
[0004] Magnetron sputtering technology is an environmentally friendly surface thin film processing technology with high film density and low resource consumption. Magnetron sputtering refers to the process of depositing atoms of metals, compounds and other substances onto the surface of the substrate to form a film by bombarding the target surface with energy particles under vacuum conditions. Compared with traditional electroplating and chemical plating technologies, the plastic substrate in magnetron sputtering technology does not need to be conductive, and the film is prepared at the atomic and molecular scale in a vacuum, with higher density, fewer defects and better performance; magnetron sputtering technology is used to prepare multilayer thin films. This method produces different colors through interference effects. The resulting thin film has a dense structure, good stability, and the color does not fade after long-term use in the environment.
[0005] Many nitride semi-transparent coatings can produce wide color gamut, never fade, non-toxic and pollution-free structural colors through thin film interference effect, and with the increase of the thickness of the semi-transparent interference layer, this structural color will change with the change of the observer's perspective, with good fantasy color effect, and the metal nitride itself has a high hardness, thus playing a good protective effect on colorful and fantasy plastic decoration. However, the applicant found in the early experiments that the direct deposition of metal compounds has poor adhesion to the plastic substrate, and it is difficult to reflect most of the visible light to the top layer, resulting in low color saturation. In addition, the melting point of plastic is lower than that of metal, and the deposition time needs to be accurately controlled. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a colorful composite film with high hardness and high bonding strength on a plastic surface and a preparation method thereof. The colorful composite film based on the plastic surface of the present invention has the characteristics of high film-base bonding strength, high hardness, high and wide color gamut, long-term stability and viewing angle variability.
[0007] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a colorful composite film with high hardness and high bonding strength on a plastic surface, which comprises a Ti seed layer, an Al layer, a TiN layer, a TiAlN layer and an AlN layer sequentially deposited on the plastic surface by magnetron sputtering.
[0008] The Al layer grows in a layer-island combined growth mode; the aluminum grain size in the Al layer is ≥100nm; the surface roughness of the Al layer is <3nm; the AlN grain size in the AlN layer is 80-150nm; and the thickness of the AlN layer is 35-180nm.
[0009] The present invention deposits Ti, Al, TiN, TiAlN and AlN on the plastic surface in sequence by magnetron sputtering. The Ti seed layer located in the first layer as an adhesion layer can greatly improve the adhesion of the subsequently deposited multilayer film, and the Al layer in the second layer is a high reflection layer, which reflects most of the visible light incident on the plastic substrate. The third layer is a TiN layer as a reflection layer and the fourth layer is a TiAlN layer as a high absorption dielectric layer. This double-layer TiAlN-TiN film acts as a broadband absorber and can present a thickness-related color, but its color gamut is narrow. For this reason, when the present invention continues to deposit the fifth layer as a semi-transparent dielectric layer AlN layer on the TiAlN-TiN absorber, the observed color can change significantly. In particular, red and green are obtained after depositing AlN, and the corresponding color gamut is significantly expanded. When the AlN layer reaches a certain thickness, the structural color generated by the thin film interference will change with the change of the observer's viewing angle, producing a fantasy effect. This colorful and fantasy nitride film has a dense surface, high color saturation and high hardness, and has an excellent protective effect on the colorful and fantasy plastic products obtained.
[0010] Specifically, the preparation principle of the high-hardness and high-bonding-force colorful composite film on the plastic surface of the present invention is: Regarding the enhancement of the film-base bonding strength: the present invention ingeniously improves the film-base bonding strength by adding a Ti seed layer as a bonding layer. This is because the plastic and Ti interface have a high reactivity, and Ti reacts with the functional groups on the plastic surface to form a large number of C-Ti and (CO)-Ti bonds, thereby improving the bonding strength between the film and the plastic. The subsequent Al aluminum layer deposited on the Ti seed layer improves the bonding strength by forming a metal bond between aluminum atoms and titanium atoms.
[0011] For the generation of structural color: a highly absorbing dielectric TiAlN layer is deposited on a TiN layer to construct a TiAlN-TiN absorber. When a semi-transparent dielectric AlN layer is deposited onto the TiAlN-TiN absorber, the obtainable color can change significantly. The multilayer film structure exhibits double resonance absorption, which greatly increases the color gamut range. This is because the semi-transparent dielectric AlN layer interacts with the light reflected on the TiAlN-TiN absorber, thereby producing interference-based colors. In this case, the color of the coating is determined not only by the electronic band structure (the refractive index of the material), but also by the geometry, that is, by the thickness of the film. As the thickness of the AlN layer increases, the color produced by interference will also show a magical effect. This is because the thickness of the top AlN layer directly determines the size of the optical path difference. Thicker AlN layers require more optical path difference to achieve interference conditions, so different angle changes will more obviously affect the observed color. If the thickness of the AlN layer is too thin, it is difficult to produce the effect of thin film interference and no color can be produced. It is just the golden yellow of the bottom layer. If the AlN layer is too thick, there will be overlapping coloring intervals at the same coating thickness, which will result in multiple light waves in a coating of one thickness. The color of the coating is a mixture of multiple colors, not a single color.
[0012] For the improvement of color brightness: First, the sputtering threshold energy of the Ti seed layer is higher than that of aluminum, and the Ti seed layer is denser and has higher hardness. Compared with the plastic substrate, it can provide a higher surface energy interface for the subsequently deposited Al layer, thereby reducing the diffusion of Al on the seeding substrate, having more nucleation sites, and reducing the pinhole defects on the surface of the Al layer. Secondly, due to the similar dissociation energy of the Al-Al bond (264 kJ / mol) and the Ti-Al bond (263 kJ / mol), the Al layer grows in a layer island bonding mode and the surface roughness is reduced. The present invention finds that the aluminum grain size deposited on the surface of the Ti seed layer is larger than that of the sample without the Ti seed layer. The larger the aluminum grain size, the fewer grain boundaries, the weakened grain boundary plasma resonance, and the reduced light scattering, so that the Al layer can provide a highly reflective substrate for the TiN-TiAlN-AlN film structure on the surface, thereby achieving the effect of improving color brightness. In addition, the present invention also finds that the Ti seed layer can not only greatly improve the adhesion of the Al layer, but also effectively reduce the surface roughness of the Al layer, avoiding defects such as pinholes, thereby further improving the reflectivity of the Al layer.
[0013] Preferably, the thickness of the Ti seed layer is 45-65 nm; the thickness of the Al layer is 20-30 nm; the thickness of the TiN layer is 45-50 nm; and the thickness of the TiAlN layer is 40-50 nm.
[0014] Preferably, the plastic is one or more of polycarbonate (PC), polymethyl methacrylate (PMMA), polyphenylene sulfide (PPS), polystyrene (PS) and polyethylene terephthalate (PET); more preferably, it is polycarbonate (PC) or polystyrene (PS).
[0015] PC not only has high strength and excellent heat resistance, but also has good weather resistance and anti-aging properties, and can be used for a long time in outdoor environments without failure. PS not only has high hardness, but also has low cost and is easy to mass produce.
[0016] In a second aspect, the present invention provides a method for preparing a colorful composite film with high hardness and high bonding strength on a plastic surface, which comprises the following steps: 1) Depositing a Ti seed layer on the plastic surface by magnetron sputtering; 2) depositing an Al layer on the surface of the Ti seed layer by magnetron sputtering; 3) depositing a TiN layer on the surface of the Al layer by magnetron sputtering; 4) depositing a TiAlN layer on the surface of the TiN layer by magnetron sputtering; 5) Depositing an AlN layer on the surface of the TiAlN layer by magnetron sputtering.
[0017] Preferably, in step 1), before depositing the Ti seed layer, the plastic surface is degreased, decontaminated and dried; the oxide layer on the surface of the titanium target and the aluminum target is removed by magnetron sputtering under inert conditions, and the plastic is surface plasma activated.
[0018] Preferably, in step 1), the deposition conditions of the Ti seed layer are: deposition current of 1.5-2.5 A, negative bias voltage of 60-100 V, and time of 8-20 min.
[0019] Preferably, in step 2), the deposition conditions of the Al layer are: target sputtering deposition, a deposition current of 2-4A, a negative bias voltage of 60-100V, and a time of 2-10min.
[0020] Preferably, in step 3), the deposition conditions of the TiN layer are: 20-40 sccm of argon and 5-10 sccm of nitrogen, Ti target deposition current of 1.5-2.5 A, Ti target negative bias of 60-100 V, Al target current of 0.2-0.4 A, and deposition time of 10-30 min.
[0021] Preferably, in step 4), the deposition conditions of the TiAlN layer are: 20-40 sccm of argon and 5-10 sccm of nitrogen; Ti target deposition current is 1.5-2.5A, Ti target negative bias voltage is 60-100V; Al target deposition current is 1-2A, deposition time is 5-15min.
[0022] Preferably, in step 5), the deposition conditions of the AlN layer are: introducing 20-40 sccm of argon and 5-10 sccm of nitrogen; the Al target deposition current is 1-2A, the Al target negative bias voltage is 60-100V, and the deposition time is 20-180min.
[0023] Preferably, in steps 3), 4) and 5), during the sputtering, all current biases are turned off every 5-50 minutes of sputtering to allow the chamber to cool.
[0024] The purpose of the above setting is to prevent the deposition process from causing the temperature inside the cavity to be too high and thus causing the plastic substrate to melt. The specific interval time is determined according to the melting point of the plastic.
[0025] Compared with the prior art, the beneficial effects of the present invention are: (1) The present invention forms a Ti seed layer and an Al layer on the plastic surface in sequence by magnetron sputtering; the Ti seed layer can greatly improve the adhesion of the Al layer, and at the same time, the Ti seed layer can also improve the density of the Al layer, reduce the surface roughness of the Al layer, and avoid defects such as pinholes, thereby improving the color brightness of the colorful composite film.
[0026] (2) The present invention constructs a pollution-free, non-fading, and highly color-saturated colorful fantasy film on the plastic surface through the thin film interference principle. As the thickness of the AlN layer increases, the color of the composite film changes with the observer's angle, resulting in a fantasy effect with saturated colors, a wide color gamut, and good stability.
[0027] (3) The present invention combines plastic with a colorful composite film and improves the surface hardness of the plastic product through the nitride ceramic film, thereby having an excellent protective effect on the plastic product. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic diagram of the structure of the colorful composite film of the present invention.
[0029] Figure 2 It is the reflection spectrum diagram of Examples 1, 2, 3, 4, 5 and 6 in the wavelength range of 380-800nm.
[0030] Figure 3 The CIE chromaticity diagram of Examples 1, 2, 3, 4, 5 and 6.
[0031] Figure 4 Digital photos of composite films on plastic surfaces: (a) Example 1, (b) Example 2, (c) Example 3, (d) Example 4, (e) Example 5, and (f) Example 6.
[0032] Figure 5 Digital photos of the colorful composite film sample in Example 6 at different observation angles: (a) 0 ° (b)22 ° 、(c)45 ° , (d) 68 ° and (e) 90 ° .
[0033] Figure 6 SEM images of highly reflective aluminum films: (a) Comparative Example 1; (b) Example 9.
[0034] Figure 7 This is the SEM image of the colorful composite film in Example 6.
[0035] Figure 8 This is an optical picture of the sample in Example 5 after the Rockwell hardness test.
[0036] Fig. 9 These are digital photos of the colored composite films on the PS plastic surface of Example 7 (left) and Example 8 (right). DETAILED DESCRIPTION
[0037] The present invention will be further described below in conjunction with the embodiments.
[0038] Overall embodiment First, a colorful composite film with high hardness and high bonding strength on a plastic surface is provided, which includes a Ti seed layer, an Al layer, a TiN layer, a TiAlN layer and an AlN layer which are sequentially deposited on the plastic surface by magnetron sputtering.
[0039] The Al layer grows in a layer-island combination growth mode; the aluminum grain size in the Al layer is ≥100 nm; the surface roughness of the Al layer is <3 nm; and the AlN grain size in the AlN layer is 80-150 nm.
[0040] In some preferred implementation cases, the thickness of the AlN layer is 35-180 nm, the thickness of the Ti seed layer is 45-50 nm; the thickness of the Al layer is 20-30 nm; the thickness of the TiN layer is 45-50 nm; and the thickness of the TiAlN layer is 40-50 nm.
[0041] In some preferred implementation cases, the plastic is one or more of polycarbonate (PC), polymethyl methacrylate (PMMA), polyphenylene sulfide (PPS), polystyrene (PS) and polyethylene terephthalate (PET); more preferably, it is polycarbonate (PC) or polystyrene (PS).
[0042] Secondly, a method for preparing a colorful composite film with high hardness and high bonding strength on a plastic surface specifically comprises the following steps: 1) Deposit a Ti seed layer on the plastic surface by magnetron sputtering.
[0043] In some preferred implementation cases, the deposition conditions of the Ti seed layer are: deposition current of 1.5-2.5A, negative bias voltage of 60-100V, and time of 8-20min. The deposition conditions of step 1) are controlled within the above range because: if the current is too low, it is easy to cause a small number of sputtered atoms and low energy, a slow film deposition rate, and low-energy atoms reaching the plastic substrate cannot spontaneously migrate to surface defects; on the contrary, if the current is too high, the number of sputtered atoms increases, the temperature inside the cavity rises sharply with the deposition time, and the plastic substrate structure is easily damaged.
[0044] In some preferred implementation cases, before depositing the Ti seed layer, the plastic surface is degreased, decontaminated and dried; the oxide layer on the surface of the titanium target and the aluminum target is removed by magnetron sputtering under inert conditions, and the plastic is surface plasma activated.
[0045] In some more preferred implementation cases, the plastic surface is first ultrasonically cleaned with chemical reagents and water to remove oil and dirt, and then dried with cold or hot air and baked.
[0046] More preferably, the chemical reagent is anhydrous ethanol, isopropanol or acetone. The drying temperature is 50-80° C. and the drying time is 120-240 min.
[0047] Further preferably, the magnetron sputtering removes the surface oxide layer of the titanium target and the aluminum target and performs surface plasma activation on the plastic, specifically comprising: fixing the plastic on a base frame in a closed unbalanced magnetron sputtering coating machine and evacuating the vacuum; filling with inert gas, and sputtering the titanium target, aluminum target and plastic with high negative bias voltage and low current.
[0048] More preferably, the vacuum degree of the vacuum pumping is 7.5×10 -6 -9.5×10 -6 Since Al is easily oxidized to aluminum oxide by oxygen in the atmosphere when deposited under low vacuum conditions, the above high vacuum conditions are sufficient to ensure the formation of a pure Al layer.
[0049] Further preferably, the high negative bias voltage is 200-500V, the low current is 0.2-0.4A; the negative bias power supply is a pulse power supply with a frequency of 200-300Hz and a pulse width of 400-600μs. If the bias voltage is too low, the ion cleaning of the plastic substrate cannot be achieved; if the bias voltage is too high, the energy of the particles impacting the plastic substrate is too high, and the plastic surface is easily damaged by heating. At the same time, if the current is too low, the target material is not easy to ignite; if the current is too high, the substrate will undergo a sputtering deposition process.
[0050] In some more preferred embodiments, during the sputtering, all current biases are turned off every 5-20 minutes of sputtering to allow the chamber to cool down.
[0051] 2) Depositing an Al layer on the surface of the Ti seed layer by magnetron sputtering.
[0052] In some preferred implementation cases, the deposition conditions of the Al layer are: using target sputtering deposition, the deposition current is 2-4A, the negative bias is 60-100V, the Ti target current is 0.2-0.4A, and the time is 2-10min. The reason for controlling the deposition conditions of step 2) in the above is: first, the sputtering deposition method with two targets placed relative to each other is used, which is conducive to improving the deposition rate and the density of the Al layer. Secondly, if the current is too low, the number of sputtered aluminum atoms is small and the energy is low, and there is not enough energy to migrate to the defects when reaching the Ti layer; on the contrary, if the current is too high, the atomic deposition rate is too fast, resulting in an increase in surface defects. Then, if the negative bias is too low, the kinetic energy of the sputtered particles is reduced, and the effect of argon ions impacting and compacting the film is weakened, but the energy of argon ions bombarding the film is too high, and the surface roughness of the film increases. Finally, if the deposition time is too short, the film density is low, and light is easy to penetrate the film; if the deposition time is long, on the one hand, the substrate is easy to heat up and damage, and on the other hand, the film growth changes from layered growth to island growth, and the roughness increases.
[0053] 3) Depositing a TiN layer on the surface of the Al layer by magnetron sputtering.
[0054] In some preferred implementation cases, the deposition conditions for depositing the TiN layer are: 20-40sccm of argon and 5-10sccm of nitrogen are introduced, the Ti target deposition current is 1.5-2.5A, the Ti target negative bias voltage is 60-100V, the Al target current is 0.2-0.4A, and the deposition time is 10-30min. The deposition conditions of step 3) are controlled as follows: first, the nitrogen flow rate is controlled to 5-10sccm, because a lower nitrogen flow rate will increase the Ti atom content in the TiN layer and reduce the purity of the TiN layer; while a higher nitrogen flow rate will cause target poisoning, which is not conducive to the deposition process. However, if the titanium target sputtering current is too high, nitrogen molecules may be sputtered out, affecting the stable supply of nitrogen source, resulting in insufficient nitrogen content in the film, an increase in the proportion of titanium element in the titanium nitride film, and the formed film may be more biased towards metallic titanium (Ti) rather than titanium nitride (TiN). If the sputtering current is too low, the bombardment of nitrogen ions may be insufficient, the nitridation reaction may be incomplete, and the resulting film may lack sufficient nitrogen content. The final film may not be true titanium nitride (TiN), but metallic titanium (Ti) or titanium oxide, etc. Finally, too high a negative bias voltage will cause high-energy ions to bombard the film surface, which may make the surface uneven and increase the surface roughness. Especially in the early stages of film growth, too high a bias voltage will cause particle aggregation and irregular growth, which may affect the optical, electrical and mechanical properties of the film. Low negative bias voltage will reduce the bombardment intensity of ions on the film surface, resulting in the inability to effectively arrange the atoms of the film. The structure of the film may become loose and have a low density. The film formed in this way has poor mechanical properties (such as hardness and wear resistance) and may appear fragile and easy to peel off.
[0055] In some more preferred embodiments, during the sputtering, all current biases are turned off every 5-30 minutes of sputtering to allow the chamber to cool down.
[0056] 4) Depositing a TiAlN layer on the surface of the TiN layer by magnetron sputtering.
[0057] In some preferred implementation cases, the deposition conditions of the TiAlN layer are: 20-40sccm of argon and 5-10sccm of nitrogen are introduced; the Ti target deposition current is 1.5-2.5A, and the Ti target negative bias voltage is 60-100V; the Al target deposition current is 1-2A, and the deposition time is 5-15min. The deposition conditions of step 4) are controlled as above because TiAlN can be changed between two materials with different optical properties: TiN is a metal-like conductive material with free electrons that can selectively absorb visible light, while AlN is a dielectric material that is transparent in the visible part of the spectrum. Therefore, by adjusting the ratio between Ti and Al, the optical constants of AlTiN can be adjusted between the metallic properties and dielectric properties of the material. TiAlN with a lower Al content is not very suitable for interference colors because too much light is easily absorbed.
[0058] In some more preferred embodiments, during the sputtering, all current biases are turned off every 5-15 minutes of sputtering to allow the chamber to cool down.
[0059] 5) Depositing an AlN layer on the surface of the TiAlN layer by magnetron sputtering.
[0060] In some preferred implementation cases, the deposition conditions of the AlN layer are: 20-40sccm of argon and 5-10sccm of nitrogen are introduced; the Al target deposition current is 1-2A, the Al target negative bias is 60-100V, and the deposition time is 20-180min. The reason for controlling the deposition conditions of step 5) as above is: the argon flow rate is controlled at 5-15sccm. This is because after the deposition is completed, the temperature in the chamber is slightly high, and a small amount of argon is introduced to prevent oxidation of the film surface. The ratio of nitrogen and argon should be strictly controlled. Although nitrogen can increase the generation of AlN, too much nitrogen will cause the nitridation reaction to be too intense and produce too many nitrogen ions. These nitrogen ions may cause excessive sputtering of the aluminum target and reduce the deposition rate of aluminum. In addition, too high a nitrogen concentration may cause the nitrogen content in the film to be too high, forming pores, cracks or other undesirable structures, affecting the density and mechanical properties of the film. Too little nitrogen may result in aluminum atoms being unable to react with enough nitrogen molecules, and the aluminum content in the deposited film being too high, which may lead to the deposition of aluminum metal phase (rather than aluminum nitride) or the production of non-ideal phases such as aluminum oxide. If the argon concentration is too high, the nitrogen concentration will be relatively low, which may lead to incomplete reaction between aluminum atoms and nitrogen atoms, inhibit the film formation process of aluminum nitride, and ultimately affect the degree of nitridation of the film, and may even result in a metallic aluminum film. If the argon concentration is too low, the working gas density is low, the deposition rate is slow, and the film density is poor.
[0061] In some more preferred embodiments, during the sputtering, all current biases are turned off every 5-30 minutes of sputtering to allow the chamber to cool down.
[0062] Specific examples and comparative examples.
[0063] Comparative Example 1 (silver-white film) (1) The PC board was cut into small discs with a diameter of 3 cm and a thickness of 3 mm as the substrate. The substrate was then ultrasonically cleaned with isopropyl alcohol and deionized water for 15 min, dried with cold and hot air, and dried in a hot oven (temperature 70 °C, time 180 min), and then fixed on the base stand of a closed unbalanced magnetron sputtering device (UDP-650). After rough vacuuming with a mechanical pump, the vacuum degree was pumped to 8.5×10 -6 torr.
[0064] (2) At room temperature, argon was filled as working gas with a flow rate of 30 sccm. The turntable speed was set to 4 r / min, the frequency of the pulse bias power supply was set to 250 Hz and the pulse width was set to 500 μs. The target and substrate were first sputtered and cleaned for 10 min with a negative bias voltage of 200 V and a low current of 0.3 A to remove the oxide layer on the surface of the Ti target and the Al target and the plasma activation on the surface of the plastic substrate.
[0065] (3) Change the current of the Al target sputtering to 2.71A and the negative bias voltage to 80V, and sputter a highly reflective Al layer on the plastic. The sputtering time is 3 minutes and the thickness is 25nm. After the sputtering process is completed, turn off the current and voltage, adjust the argon gas flow rate to 10sccm, and the duration is 15 minutes. Then turn off the coating program and wait for the chamber to cool to room temperature before taking it out.
[0066] Example 1 (blue-purple composite film) (1) The PC board was cut into small discs with a diameter of 3 cm and a thickness of 3 mm as the substrate. The substrate was then ultrasonically cleaned with isopropyl alcohol and deionized water for 15 min, dried with cold and hot air, and dried in a hot oven (temperature 70 °C, time 180 min), and then fixed on the base stand of a closed unbalanced magnetron sputtering device (UDP-650). After rough vacuuming with a mechanical pump, the vacuum degree was pumped to 8.5×10 -6 torr.
[0067] (2) At room temperature, argon was filled as working gas with a flow rate of 30 sccm. The turntable speed was set to 4 r / min, the frequency of the pulse bias power supply was set to 250 Hz and the pulse width was set to 500 μs. The target and substrate were first sputtered and cleaned for 10 min with a negative bias voltage of 200 V and a low current of 0.3 A to remove the oxide layer on the surface of the Ti target and the Al target and the plasma activation on the surface of the plastic substrate.
[0068] (3) Change the current on the Ti target to 2.47 A and the negative bias voltage to 80 V. First, sputter the Ti seed layer with a sputtering time of 14 min and a thickness of 55 nm. Then adjust the current of the Ti target back to 0.3 A.
[0069] (4) Change the current of the Al target sputtering to 2.71A and the negative bias voltage to 80V, and sputter a high reflective Al layer on the Ti seed layer. The sputtering time is 3min and the thickness is 25nm. Without breaking the vacuum, turn off all target currents. After the chamber is cooled for 1h, introduce argon and nitrogen at flow rates of 30sccm and 7sccm respectively. Turn on the Ti target current to 2.1A and the low Al target current to 0.3A. Sputter a TiN layer. The sputtering time is 20min and the thickness is 48nm. Turn off all target currents and bias voltages.
[0070] (5) After the chamber has cooled for 1 hour, 30 sccm of argon and 7 sccm of nitrogen are introduced, and the Al target current is 1.56A and the Ti target current is 2.1A. The bias voltage is -80V, and the TiAlN layer is sputtered for 10 minutes with a thickness of 45nm. The Ti target current is lowered to 0.3A, and the Al target current is turned on to 1.56A. The AlN layer is sputtered for 37 minutes with a thickness of 37nm. During the sputtering process, all current biases are turned off every 20 minutes of sputtering of the AlN layer, and the chamber is cooled for 1 hour. After the sputtering process is completed, the current and voltage are turned off, and the argon flow rate is adjusted to 10 sccm for 15 minutes. Then the coating program is turned off and the chamber is taken out after cooling to room temperature.
[0071] Example 2 (Mori Green Composite Film) (1) The PC board was cut into small discs with a diameter of 3 cm and a thickness of 3 mm as the substrate. The substrate was then ultrasonically cleaned with isopropyl alcohol and deionized water for 15 min, dried with cold and hot air, and dried in a hot oven (temperature 70 °C, time 180 min), and then fixed on the base stand of a closed unbalanced magnetron sputtering device (UDP-650). After rough vacuuming with a mechanical pump, the vacuum degree was pumped to 8.5×10 -6 torr.
[0072] (2) At room temperature, argon was filled as working gas with a flow rate of 30 sccm. The turntable speed was set to 4 r / min, the frequency of the pulse bias power supply was set to 250 Hz and the pulse width was set to 500 μs. The target and substrate were first sputtered and cleaned for 10 min with a negative bias voltage of 200 V and a low current of 0.3 A to remove the oxide layer on the surface of the Ti target and the Al target and the plasma activation on the surface of the plastic substrate.
[0073] (3) Change the current on the Ti target to 2.47 A and the negative bias voltage to 80 V. First, sputter the Ti seed layer with a sputtering time of 14 min and a thickness of 55 nm. Then adjust the current of the Ti target back to 0.3 A.
[0074] (4) Change the current of the Al target to 2.71A and the negative bias voltage to 80V, and sputter a high reflective Al layer on the Ti seed layer. The sputtering time is 3min and the thickness is 25nm. Without breaking the vacuum, turn off all target currents. After the chamber is cooled for 1h, introduce argon and nitrogen at flow rates of 30sccm and 7sccm respectively. Turn on the Ti target current to 2.1A and the low Al target current to 0.3A. Sputter a TiN layer. The sputtering time is 20min and the thickness is 48nm. Turn off all target currents and bias voltages.
[0075] (5) After the chamber has cooled for 1 hour, 30 sccm of argon and 7 sccm of nitrogen are introduced, and the Al target current is 1.56A and the Ti target current is 2.1A. The bias voltage is -80V, and the TiAlN layer is sputtered for 10 minutes with a thickness of 45nm. The Ti target current is lowered to 0.3A, and the Al target current is turned on to 1.56A. The AlN layer is sputtered for 61 minutes with a thickness of 61nm. During the sputtering process, all current biases are turned off every 20 minutes of sputtering of the AlN layer, and the chamber is cooled for 1 hour. After the sputtering process is completed, the current and voltage are turned off, and the argon flow rate is adjusted to 10 sccm for 15 minutes. Then the coating program is turned off and the chamber is taken out after cooling to room temperature.
[0076] Example 3 (yellow-green composite film) (1) The PC board was cut into small discs with a diameter of 3 cm and a thickness of 3 mm as the substrate. The substrate was then ultrasonically cleaned with isopropyl alcohol and deionized water for 15 min, dried with cold and hot air, and dried in a hot oven (temperature 70 °C, time 180 min), and then fixed on the base stand of a closed unbalanced magnetron sputtering device (UDP-650). After rough vacuuming with a mechanical pump, the vacuum degree was pumped to 8.5×10 -6 torr.
[0077] (2) At room temperature, argon was filled as working gas with a flow rate of 30 sccm. The turntable speed was set to 4 r / min, the frequency of the pulse bias power supply was set to 250 Hz and the pulse width was set to 500 μs. The target and substrate were first sputtered and cleaned for 10 min with a negative bias voltage of 200 V and a low current of 0.3 A to remove the oxide layer on the surface of the Ti target and the Al target and the plasma activation on the surface of the plastic substrate.
[0078] (3) Change the current on the Ti target to 2.47 A and the negative bias voltage to 80 V. First, sputter the Ti seed layer with a sputtering time of 14 min and a thickness of 55 nm. Then adjust the current of the Ti target back to 0.3 A.
[0079] (4) Change the current of the Al target to 2.71A and the negative bias voltage to 80V, and sputter a high reflective Al layer on the Ti seed layer. The sputtering time is 3min and the thickness is 25nm. Without breaking the vacuum, turn off all target currents. After the chamber is cooled for 1h, introduce argon and nitrogen at flow rates of 30sccm and 7sccm respectively. Turn on the Ti target current to 2.1A and the low Al target current to 0.3A. Sputter a TiN layer. The sputtering time is 20min and the thickness is 48nm. Turn off all target currents and bias voltages.
[0080] (5) After the chamber has cooled for 1 hour, 30 sccm of argon and 7 sccm of nitrogen are introduced, and the Al target current is 1.56A and the Ti target current is 2.1A. The bias voltage is -80V, and the TiAlN layer is sputtered for 10 minutes with a thickness of 45nm. The Ti target current is lowered to 0.3A, and the Al target current is turned on to 1.56A. The AlN layer is sputtered for 75 minutes with a thickness of 75nm. During the sputtering process, all current biases are turned off every 20 minutes of sputtering of the AlN layer, and the chamber is cooled for 1 hour. After the sputtering process is completed, the current and voltage are turned off, and the argon flow rate is adjusted to 10 sccm for 15 minutes. Then the coating program is turned off and the chamber is taken out after cooling to room temperature.
[0081] Example 4 (golden composite film) (1) The PC board was cut into small discs with a diameter of 3 cm and a thickness of 3 mm as the substrate. The substrate was then ultrasonically cleaned with isopropyl alcohol and deionized water for 15 min, dried with cold and hot air, and dried in a hot oven (temperature 70 °C, time 180 min), and then fixed on the base stand of a closed unbalanced magnetron sputtering device (UDP-650). After rough vacuuming with a mechanical pump, the vacuum degree was pumped to 8.5×10 -6 torr.
[0082] (2) At room temperature, argon was filled as working gas with a flow rate of 30 sccm. The turntable speed was set to 4 r / min, the frequency of the pulse bias power supply was set to 250 Hz and the pulse width was set to 500 μs. The target and substrate were first sputtered and cleaned for 10 min with a negative bias voltage of 200 V and a low current of 0.3 A to remove the oxide layer on the surface of the Ti target and the Al target and the plasma activation on the surface of the plastic substrate.
[0083] (3) Change the current on the Ti target to 2.47 A and the negative bias voltage to 80 V. First, sputter the Ti seed layer with a sputtering time of 14 min and a thickness of 55 nm. Then adjust the current of the Ti target back to 0.3 A.
[0084] (4) Change the current of the Al target to 2.71A and the negative bias voltage to 80V, and sputter a high reflective Al layer on the Ti seed layer. The sputtering time is 3min and the thickness is 25nm. Without breaking the vacuum, turn off all target currents. After the chamber is cooled for 1h, introduce argon and nitrogen at flow rates of 30sccm and 7sccm respectively. Turn on the Ti target current to 2.1A and the low Al target current to 0.3A. Sputter a TiN layer. The sputtering time is 20min and the thickness is 48nm. Turn off all target currents and bias voltages.
[0085] (5) After the chamber has cooled for 1 hour, 30 sccm of argon and 7 sccm of nitrogen are introduced, and the Al target current is 1.56A and the Ti target current is 2.1A. The bias voltage is -80V, and the TiAlN layer is sputtered for 10 minutes with a thickness of 45nm. The Ti target current is lowered to 0.3A, and the Al target current is turned on to 1.56A. The AlN layer is sputtered for 110 minutes with a thickness of 110 minutes. During the sputtering process, all current biases are turned off every 20 minutes of sputtering of the AlN layer, and the chamber is cooled for 1 hour. After the sputtering process is completed, the current and voltage are turned off, and the argon flow rate is adjusted to 10 sccm for 15 minutes. Then the coating program is turned off and the chamber is taken out after cooling to room temperature.
[0086] Example 5 (orange-yellow composite film) (1) The PC board was cut into small discs with a diameter of 3 cm and a thickness of 3 mm as the substrate. The substrate was then ultrasonically cleaned with isopropyl alcohol and deionized water for 15 min, dried with cold and hot air, and dried in a hot oven (temperature 70 °C, time 180 min), and then fixed on the base stand of a closed unbalanced magnetron sputtering device (UDP-650). After rough vacuuming with a mechanical pump, the vacuum degree was pumped to 8.5×10 -6 torr.
[0087] (2) At room temperature, argon was filled as working gas with a flow rate of 30 sccm. The turntable speed was set to 4 r / min, the frequency of the pulse bias power supply was set to 250 Hz and the pulse width was set to 500 μs. The target and substrate were first sputtered and cleaned for 10 min with a negative bias voltage of 200 V and a low current of 0.3 A to remove the oxide layer on the surface of the Ti target and the Al target and the plasma activation on the surface of the plastic substrate.
[0088] (3) Change the current on the Ti target to 2.47 A and the negative bias voltage to 80 V. First, sputter the Ti seed layer with a sputtering time of 14 min and a thickness of 55 nm. Then adjust the current of the Ti target back to 0.3 A.
[0089] (4) Change the current of the Al target to 2.71A and the negative bias voltage to 80V, and sputter a high reflective Al layer on the Ti seed layer. The sputtering time is 3min and the thickness is 25nm. Without breaking the vacuum, turn off all target currents. After the chamber is cooled for 1h, introduce argon and nitrogen at flow rates of 30sccm and 7sccm respectively. Turn on the Ti target current to 2.1A and the low Al target current to 0.3A. Sputter a TiN layer. The sputtering time is 20min and the thickness is 48nm. Turn off all target currents and bias voltages.
[0090] (5) After the chamber has cooled for 1 hour, 30 sccm of argon and 7 sccm of nitrogen are introduced, and the Al target current is 1.56A and the Ti target current is 2.1A. The bias voltage is -80V, and the TiAlN layer is sputtered for 10 minutes with a thickness of 45nm. The Ti target current is lowered to 0.3A, and the Al target current is turned on to 1.56A. The AlN layer is sputtered for 130 minutes with a thickness of 130nm. During the sputtering process, all current biases are turned off every 20 minutes of sputtering of the AlN layer, and the chamber is cooled for 1 hour. After the sputtering process is completed, the current and voltage are turned off, and the argon flow rate is adjusted to 10 sccm for 15 minutes. Then the coating program is turned off and the chamber is taken out after cooling to room temperature.
[0091] Example 6 (Colorful composite film) (1) The PC board was cut into small discs with a diameter of 3 cm and a thickness of 3 mm as the substrate. The substrate was then ultrasonically cleaned with isopropyl alcohol and deionized water for 15 min, dried with cold and hot air, and dried in a hot oven (temperature 70 °C, time 180 min), and then fixed on the base stand of a closed unbalanced magnetron sputtering device (UDP-650). After rough vacuuming with a mechanical pump, the vacuum degree was pumped to 8.5×10 -6 torr.
[0092] (2) At room temperature, argon was filled as working gas with a flow rate of 30 sccm. The turntable speed was set to 4 r / min, the frequency of the pulse bias power supply was set to 250 Hz and the pulse width was set to 500 μs. The target and substrate were first sputtered and cleaned for 10 min with a negative bias voltage of 200 V and a low current of 0.3 A to remove the oxide layer on the surface of the Ti target and the Al target and the plasma activation on the surface of the plastic substrate.
[0093] (3) Change the current on the Ti target to 2.47 A and the negative bias voltage to 80 V. First, sputter the Ti seed layer with a sputtering time of 14 min and a thickness of 55 nm. Then adjust the current of the Ti target back to 0.3 A.
[0094] (4) Change the current of the Al target to 2.71A and the negative bias voltage to 80V, and sputter a high reflective Al layer on the Ti seed layer. The sputtering time is 3min and the thickness is 25nm. Without breaking the vacuum, turn off all target currents. After the chamber is cooled for 1h, introduce argon and nitrogen at flow rates of 30sccm and 7sccm respectively. Turn on the Ti target current to 2.1A and the low Al target current to 0.3A. Sputter a TiN layer. The sputtering time is 20min and the thickness is 48nm. Turn off all target currents and bias voltages.
[0095] (5) After the chamber has cooled for 1 hour, 30 sccm of argon and 7 sccm of nitrogen are introduced, and the Al target current is 1.56A and the Ti target current is 2.1A. The bias voltage is -80V, and the TiAlN layer is sputtered for 10 minutes with a thickness of 45nm. The Ti target current is lowered to 0.3A, and the Al target current is turned on to 1.56A. The AlN layer is sputtered for 180 minutes with a thickness of 180nm. During the sputtering process, all current biases are turned off every 20 minutes of sputtering of the AlN layer, and the chamber is cooled for 1 hour. After the sputtering process is completed, the current and voltage are turned off, and the argon flow rate is adjusted to 10 sccm for 15 minutes. Then the coating program is turned off and the chamber is taken out after cooling to room temperature.
[0096] Example 7 (purple-blue composite film) (1) The PS plate was cut into small discs with a diameter of 3 cm and a thickness of 3 mm as the substrate. The substrate was then ultrasonically cleaned with anhydrous ethanol and deionized water for 15 min, dried with cold and hot air, and dried in a hot oven (temperature 60 °C, time 180 min), and then fixed on the base stand of a closed unbalanced magnetron sputtering device (UDP-650). After rough vacuuming with a mechanical pump, the vacuum degree was pumped to 8.5×10 -6 torr.
[0097] (2) At room temperature, argon was filled as working gas with a flow rate of 30 sccm. The turntable speed was set to 4 r / min, the frequency of the pulse bias power supply was set to 250 Hz and the pulse width was set to 500 μs. The target and substrate were first sputtered and cleaned for 10 min with a negative bias voltage of 200 V and a low current of 0.3 A to remove the oxide layer on the surface of the Ti target and the Al target and the plasma activation on the surface of the plastic substrate.
[0098] (3) Change the current on the Ti target to 2.47 A and the negative bias voltage to 80 V. First, sputter the Ti seed layer for 14 min with a thickness of 55 nm. The deposition is divided into two times, each time for 7 min. Then, turn off the current of the Ti target and cool the chamber for 1 h.
[0099] (4) Change the current of the Al target to 2.71A and the negative bias voltage to 80V, and sputter a high reflective Al layer on the Ti seed layer for 3 minutes with a thickness of 25nm. Without breaking the vacuum, turn off all target currents. After the chamber is cooled for 1 hour, introduce argon and nitrogen with flow rates of 30sccm and 7sccm respectively. Turn on the Ti target current to 2.1A and the low Al target current to 0.3A, and sputter a TiN layer for 20 minutes with a thickness of 48nm. The deposition is divided into two times, each time for 10 minutes, and turn off all target currents and bias voltages.
[0100] (5) After the chamber has cooled for 1 hour, 30 sccm of argon and 7 sccm of nitrogen are introduced, and the Al target current is 1.56A and the Ti target current is 2.1A. The bias voltage is -80V, and the TiAlN layer is sputtered for 10 minutes with a thickness of 45nm. The Ti target current is lowered to 0.3A, and the Al target current is turned on to 1.56A. The AlN layer is sputtered for 31 minutes with a thickness of 31nm. During the sputtering process, all current biases are turned off every 9 minutes of sputtering of the AlN layer, and the chamber is cooled for 1 hour. After the sputtering process is completed, the current and voltage are turned off, and the argon flow rate is adjusted to 10 sccm for 15 minutes. Then the coating program is turned off and the chamber is taken out after cooling to room temperature.
[0101] Example 8 (Sky blue composite film) (1) The PS plate was cut into small discs with a diameter of 3 cm and a thickness of 3 mm as the substrate. The substrate was then ultrasonically cleaned with anhydrous ethanol and deionized water for 15 min, dried with cold and hot air, and dried in a hot oven (temperature 60 °C, time 180 min), and then fixed on the base stand of a closed unbalanced magnetron sputtering device (UDP-650). After rough vacuuming with a mechanical pump, the vacuum degree was pumped to 8.5×10 -6 torr.
[0102] (2) At room temperature, argon was filled as working gas with a flow rate of 30 sccm. The turntable speed was set to 4 r / min, the frequency of the pulse bias power supply was set to 250 Hz and the pulse width was set to 500 μs. The target and substrate were first sputtered and cleaned for 10 min with a negative bias voltage of 200 V and a low current of 0.3 A to remove the oxide layer on the surface of the Ti target and the Al target and the plasma activation on the surface of the plastic substrate.
[0103] (3) Change the current on the Ti target to 2.47 A and the negative bias voltage to 80 V. First, sputter the Ti seed layer for 14 min with a thickness of 55 nm. The deposition is divided into two times, each time for 7 min. Then, turn off the current of the Ti target and cool the chamber for 1 h.
[0104] (4) Change the current of the Al target to 2.71A and the negative bias voltage to 80V, and sputter a high reflective Al layer on the Ti seed layer for 3 minutes with a thickness of 25nm. Without breaking the vacuum, turn off all target currents. After the chamber is cooled for 1 hour, introduce argon and nitrogen with flow rates of 30sccm and 7sccm respectively. Turn on the Ti target current to 2.1A and the low Al target current to 0.3A, and sputter a TiN layer for 20 minutes with a thickness of 48nm. The deposition is divided into two times, each time for 10 minutes, and turn off all target currents and bias voltages.
[0105] (5) After the chamber has cooled for 1 hour, argon gas of 30 sccm and nitrogen gas of 7 sccm are introduced, and the Al target current of 1.56A and the Ti target current of 2.1A are turned on at the same time, and the bias voltage is -80V. The TiAlN layer is sputtered for 10 minutes with a thickness of 45nm. The Ti target current is lowered to 0.3A, and the Al target current is turned on to 1.56A. The AlN layer is sputtered for 41 minutes with a thickness of 41nm. During the sputtering process, all current biases are turned off every 9 minutes of sputtering of the AlN layer, and the chamber is cooled for 1 hour. After the sputtering process is completed, the current and voltage are turned off, and the argon gas flow rate is adjusted to 10 sccm for a duration of 15 minutes. Then the coating program is turned off and the chamber is taken out after cooling to room temperature.
[0106] Example 9 (Silver-white composite film) (1) The PC board was cut into small discs with a diameter of 3 cm and a thickness of 3 mm as the substrate. The substrate was then ultrasonically cleaned with isopropyl alcohol and deionized water for 15 min, dried with cold and hot air, and dried in a hot oven (temperature 70 °C, time 180 min), and then fixed on the base stand of a closed unbalanced magnetron sputtering device (UDP-650). After rough vacuuming with a mechanical pump, the vacuum degree was pumped to 8.5×10 -6 torr.
[0107] (2) At room temperature, argon was filled as working gas with a flow rate of 30 sccm. The turntable speed was set to 4 r / min, the frequency of the pulse bias power supply was set to 250 Hz and the pulse width was set to 500 μs. The target and substrate were first sputtered and cleaned for 10 min with a negative bias voltage of 200 V and a low current of 0.3 A to remove the oxide layer on the surface of the Ti target and the Al target and the plasma activation on the surface of the plastic substrate.
[0108] (3) Change the current on the Ti target to 2.47 A and the negative bias voltage to 80 V. First, sputter the Ti seed layer with a sputtering time of 14 min and a thickness of 55 nm. Then adjust the current of the Ti target back to 0.3 A.
[0109] (4) Change the current of the Al target to 2.71A and the negative bias voltage to 80V, and sputter a highly reflective Al layer on the Ti seed layer. The sputtering time is 3 minutes and the thickness is 25nm. After the sputtering process is completed, turn off the current and voltage, adjust the argon gas flow rate to 10sccm, and the duration is 15 minutes. Then turn off the coating program and take it out after the chamber cools to room temperature.
[0110] Performance Testing and Characterization Figure 1 Schematic diagram of the structure of the colorful composite film of the present invention. Figure 1 As shown, the film structure is a multilayer film structure, in which the Ti seed layer is used as an adhesive layer to improve the film-base bonding strength; and the Al layer is used as a reflective layer to improve the color brightness. If a translucent AlN layer is simply deposited, visible light is difficult to be reflected to the top layer, and the effect of thin film interference cannot be produced. When a highly absorbing medium TiAlN layer is deposited on a thinner TiN to construct a TiAlN-TiN absorber, and then an ultra-thin translucent dielectric layer AlN layer is deposited on the TiAlN-TiN absorber, different colors can be obtained. The results show that the colorful fantasy composite film designed by the present invention has a multilayer film structure, and a variety of colors can be obtained by improving the bonding strength through the Ti seed layer, improving the color brightness of the sample through the Al layer, and obtaining a variety of colors through the multilayer thin film interference effect.
[0111] Figure 2 : is the reflection spectrum of Examples 1, 2, 3, 4, 5 and 6 in the wavelength range of 380-800nm. Figure 2 As shown, the corresponding reflectances of Examples 1, 2, 3, 4, 5 and 6 are at 450nm, 502nm, 552nm, 598nm and 757nm, respectively, and the colors are blue-purple, forest green, yellow-green, golden yellow, orange-yellow and rose-red, respectively. The maximum reflectance can reach 68%, which shows that the PC surface composite film has good color brightness. In Examples 1, 2, 3, 4, 5 and 6, only the thickness of the topmost AlN layer is different, and the color is generated by the thin film interference of the top layer. The results show that a variety of colors can be obtained by generating thin film interference through a multilayer film structure, and the color changes with the thickness of the top AlN layer.
[0112] Figure 3 is the CIE chromaticity diagram of Examples 1, 2, 3, 4, 5 and 6. Figure 3As shown in the figure, the color of the sample almost covers the entire color gamut. As the deposition time of the top AlN layer increases, the thickness of the AlN layer increases, and the color changes in the direction of the blue arrow in the chromatogram, that is, from purple to red. This color change is a typical thin film interference behavior. The results show that the composite film made of the three-layer film structure has the advantages of high chromaticity and wide color gamut.
[0113] Figure 4 The digital photos of the composite films on the plastic surface are as follows: (a) Example 1, (b) Example 2, (c) Example 3, (d) Example 4, (e) Example 5 and (f) Example 6. Figure 4 As shown, the color of Example 1 is blue-purple, the color of Example 2 is forest green, the color of Example 3 is yellow-green, the color of Example 4 is golden yellow, the color of Example 5 is orange-yellow, and the color of Example 6 is rose red. This corresponds to Curve 3 in the reflection spectrum. The results show that the composite film made of the multilayer film structure has bright colors and high color saturation.
[0114] Figure 5 Digital photos of the colorful composite film sample in Example 6 at different observation angles: (a) 0 ° (b)22 ° 、(c)45 ° , (d) 68 ° and (e) 90 ° .like Figure 5 As shown, when the shooting angle changes from 0 ° Transition to 90 ° When the thickness of the AlN layer increases, the range of interference color changes will also increase. Because thicker AlN layers require more optical path differences to achieve interference conditions, different angle changes will more obviously affect the observed color. The results show that the color of the sample made of a multilayer film structure will show a fantasy color effect as the thickness of the top AlN layer increases.
[0115] Figure 6 The SEM images of the highly reflective aluminum film are as follows: (a) Comparative Example 1 and (b) Example 9. Figure 6As shown, the single grains on the surface layer of the single-layer aluminum film (Al) in Comparative Example 1 are small and clearly visible, with obvious grain boundaries and obvious light and dark contrast changes. In contrast, the surface of the aluminum film with a titanium seed layer in Example 9 is smooth and dense, the grain boundaries are not obvious, and there is no obvious light and dark contrast change. This shows that the aluminum film in Comparative Example 1 conforms to the Volmer-Weber model growth, that is, the initial growth mode is isolated islands, which leads to an increase in the surface roughness of the aluminum film. In Example 9, due to the close bond energy of Al-Al (264 kJ / mol) and Ti-Al (263 kJ / mol), the growth mode of the aluminum film is transformed from island growth to layer-island combination growth mode, which reduces the surface roughness. This is also consistent with the fact that the aluminum film (1.160 J / m 2 ) is related to the surface free energy of the film deposition surface, titanium (1.989 J / m 2 ) is significantly higher than the surface free energy of pristine polycarbonate (0.38 J / m 2 ), Example 9 deposits aluminum on a titanium seed layer with high surface free energy, reduces the diffusion of aluminum atoms on the substrate, and has more nucleation sites. The results show that the addition of a titanium seed layer leads to a more layered growth mechanism, reduces the surface roughness of the film, increases the number of nucleation sites, reduces the diffusion of aluminum atoms, and improves the reflectivity of the film.
[0116] Figure 7 : is a SEM image of the colorful composite film in Example 6. Figure 7 As shown, the surface of the AlN layer (a) in Example 6 is very smooth, and almost no defects such as pinholes, cracks or large particles can be seen in the entire area. This smooth surface structure is conducive to the coating reflecting visible light, while the surface morphology of the AlN layer (b) in Example 6 after magnification at a high magnification shows that many small particles are evenly distributed on the surface of the film, and the particle size is uniform, with an average size of about 37nm, and the arrangement is regular and uniform, which indicates that the film structure is very dense. The particle size range of the AlN grains in Example 6 measured by Nano Measurer software is 95-135nm. The results show that the AlN layer prepared by magnetron sputtering has a smooth surface, a dense structure, good crystallization, and uniform thickness, and has the conditions for thin film interference with visible light.
[0117] Figure 8 This is an optical picture of Example 5 after the Rockwell hardness test. Figure 8 As shown in the figure, after the sample was pressed by the Rockwell hardness tester, no obvious shedding was observed under the microscope. When the local surface was magnified, only very small radial cracks were observed, which shows that the multilayer film structure has very good film-base bonding with the plastic substrate. The results show that the addition of the Ti seed layer provides a transition layer between the metal nitride film and the plastic substrate, greatly improving the film-base bonding.
[0118] Fig. 9For Example 7 ( Fig. 9 Sample on the left) and Example 8 ( Fig. 9 Digital photo of the colored composite film on the PS plastic surface (sample on the right). Fig. 9 As shown, Example 7 ( Fig. 9 The sample color in Example 8 ( Fig. 9 The sample on the right is sky blue, the PS plastic surface coating is dense and smooth, without obvious defects, bright and colorful, and has high color saturation. The results show that the preparation method of this color composite film is applicable to different plastics, and the color produced still has high color saturation.
[0119] Table 1 shows the microhardness values of the original PC, PS and Examples 1, 2, 3, 4, 5, 6, 7 and 8. A square-conical diamond indenter with a load of 0.098 N and a relative angle of 136° was used to press into the sample surface on a Vickers hardness tester. After holding for a specified time, the diagonal length of the indentation was measured, and the hardness (HV) was calculated according to the formula.
[0120]
[0121] F = load (N) S = indentation surface area (mm 2 ) α = angle between the indenter faces = 136° d = average diagonal length of indentation (mm) From the data in Table 1, we can see that the hardness of the original PC and PS is 14.51 kgf / mm 2 and 23.55 kgf / mm 2 , while the hardness of the PC plastic surface composite film in Examples 1, 2, 3, 4, 5 and 6 is 17.16 kgf / mm 2 、17.36kgf / mm 2 、17.56 kgf / mm 2 、17.77 kgf / mm 2 、18.47 kgf / mm 2 and 19.97 kgf / mm 2 , which are higher than the hardness of the original PC. The hardness of the PS surface composite film in Examples 7 and 8 is 25.68 kgf / mm 2 and 26.13 kgf / mm 2 , which is also higher than the hardness value of the original PS, indicating that the deposited composite film can improve the surface hardness of the plastic and has a good protective effect on plastic products.
[0122] Table 1
[0123] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0124] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A colorful composite film with high hardness and high bonding strength on a plastic surface, characterized in that: The method comprises a Ti seed layer, an Al layer, a TiN layer, a TiAlN layer and an AlN layer which are sequentially deposited on the plastic surface by magnetron sputtering; The growth mode of the Al layer is a layer-island combined growth mode; The AlN grain size in the AlN layer = 80-150 nm; The thickness of the AlN layer is 35-180 nm.
2. The plastic surface high hardness and high bonding strength colorful composite film according to claim 1, characterized in that: The thickness of the Ti seed layer is 45-65 nm; The thickness of the Al layer is 20-30 nm; The thickness of the TiN layer is 45-50 nm; The thickness of the TiAlN layer is 40-50 nm.
3. The plastic surface high hardness and high bonding strength colorful composite film according to claim 1, characterized in that: The plastic is one or more of polycarbonate, polymethyl methacrylate, polyphenylene sulfide, polystyrene and polyethylene terephthalate.
4. A method for preparing a colorful composite film with high hardness and high bonding strength on a plastic surface according to any one of claims 1 to 3, characterized in that include: 1) Depositing a Ti seed layer on the plastic surface by magnetron sputtering; 2) depositing an Al layer on the surface of the Ti seed layer by magnetron sputtering; 3) depositing a TiN layer on the surface of the Al layer by magnetron sputtering; 4) depositing a TiAlN layer on the surface of the TiN layer by magnetron sputtering; 5) Depositing an AlN layer on the surface of the TiAlN layer by magnetron sputtering.
5. The preparation method according to claim 4, characterized in that: In step 1), before depositing the Ti seed layer, the plastic surface is degreased, decontaminated and dried; the oxide layer on the surface of the titanium target and the aluminum target is removed by magnetron sputtering under inert conditions, and the plastic is surface plasma activated.
6. The preparation method according to claim 4, characterized in that: In step 1), the deposition conditions of the Ti seed layer are: deposition current of 1.5-2.5A, negative bias voltage of 60-100V, and time of 8-20min.
7. The preparation method according to claim 4, characterized in that: In step 2), the deposition conditions of the Al layer are: target sputtering deposition, deposition current of 2-4A, negative bias voltage of 60-100V, and time of 2-10min.
8. The preparation method according to claim 4, characterized in that: In step 3), the deposition conditions of the TiN layer are: 20-40 sccm of argon and 5-10 sccm of nitrogen, Ti target deposition current of 1.5-2.5 A, Ti target negative bias of 60-100 V, Al target current of 0.2-0.4 A, and deposition time of 10-30 min.
9. The preparation method according to claim 4, characterized in that: In step 4), the deposition conditions of the TiAlN layer are: 20-40 sccm of argon and 5-10 sccm of nitrogen; Ti target deposition current is 1.5-2.5A, Ti target negative bias voltage is 60-100V; Al target deposition current is 1-2A, and deposition time is 5-15min.
10. The preparation method according to claim 4, characterized in that: In step 5), the deposition conditions of the AlN layer are: 20-40 sccm of argon and 5-10 sccm of nitrogen; Al target deposition current is 1-2A, Al target negative bias voltage is 60-100V, and deposition time is 20-180min.
Citation Information
Patent Citations
High-temperature-resisting solar selective absorption coating and manufacture method thereof
CN103234293A
Ti / TiN / TiAlN composite coating on surface of cutting tool material and preparation method of Ti / TiN / TiAlN composite coating
CN103334082A
Wear-resistant ultrathin color optical coating structure and preparation method thereof
CN116970901A
Sputtered woven fabric having interactive rainbow colors
JP1995252773A
Method of producing structural coloring body utilizing surface ruggedness, and structural coloring body utilizing surface ruggedness
JP2005194595A